2015
DOI: 10.4314/bajopas.v7i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative leaching of a Nigerian chalcopyrite ore by nitric acid

Abstract: Due to increasing uses of copper nitrate, Cu(NO 3 ) 2 , as catalysts, textile and polishing agents for other metals, experiment on the leaching of a Nigerian chalcopyrite ore by nitric acid for possible production of copper nitrate was examined. The effects of acid concentration, temperature and particle size on the dissolution rates of chalcopyrite ore have been investigated. Distribution of elements, compounds present within the ore particle size -90 + 75 µm was initially determined by X-ray Fluorescence (XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…As the analyses progresses it could be observed that as the leaching time increases the percentage degree of reduction of sulphur content increases. The results obtained from the experiments agreed with [9] which observed that the percentage reduction sulphur is directly proportional to leaching time.…”
Section: Development Of Statistical Multivariable Modelssupporting
confidence: 81%
See 3 more Smart Citations
“…As the analyses progresses it could be observed that as the leaching time increases the percentage degree of reduction of sulphur content increases. The results obtained from the experiments agreed with [9] which observed that the percentage reduction sulphur is directly proportional to leaching time.…”
Section: Development Of Statistical Multivariable Modelssupporting
confidence: 81%
“…The removal of sulphur from iron and steel presents problems because of similarity of the standard free energies of formation of iron oxide and sulphur pentoxide [9]. Consequently, in the reducing conditions of the blast furnace to recover some 99.5% of the iron charged, near complete reduction of sulphur pentoxide from the acid blast furnace occurs.…”
Section: Purpose and Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dilute acid leaching has been shown to be efficient leaching reagents. Alafara et al (2005) have quantitatively evaluated leaching dissolution of Itakpe iron ore in hydrochloric acid [7]. Adeleke et al [8].…”
Section: Resultsmentioning
confidence: 99%